(untitled) (KULT_online, 2011)
This interdisciplinary volume investigates potential analogies between figures of mystical and religious thought and language, on the one hand, and phenomena of aesthetic creativity and reception in the 20th century, on the other. The individual contributions explore common characteristics of mystical and aesthetic thought, experience and (re)presentation on the level of theory as well as through exemplary case studies of literary works and films by, for example, Paul Celan, Gamal al-Ghitani, Cynthia Ozick, Marcel Proust, and Michelangelo Antonioni. By highlighting such very diverse individual figures and phenomena, the volume reveals a broad spectrum of possible analogies between mysticism and modern aesthetics and makes visible some further potentials of this challenging area of research.